Histopathological alterations and microorganism presents in Rattus norvegicus infected with Angiostrongylus cantonensis - Solórzano Alava, Luis (2018)
Rats (Rattus sp) are the definitive hosts of the nematode Angiostrongylus cantonensis. The objective of this study was to identify the organs affected by the presence of A. cantonensis (adults) and the type of damage caused, as well as to establish the presence of microorganisms (bacteria and fungi) that could be found in these lesions. The study was conducted in 2014-2016 with 65 specimens (60 infected in the laboratory, which presented the larva L1 in their stools and 5 uninfected as a control group). Pulmonary and cardiac tissue samples were obtained on different post-infection days (dpi), stained with Gram and cultured on horse blood agar, MacConkey agar, Thioglycolate medium, Cystin medium Triptein Agar (CTA). Macro and microscopic alterations in pulmonary and cardiac tissue were observed, as well as microorganisms in lung lesions in both Gram and bacteriological cultures. Hardened lung tissue, polynuclear cells, pus, color changes in the pericardium and alterations in the weight of the organs were observed. In conclusion, the rats infected with Angiostrongylus cantonensis presented a variety of histological alterations in their internal organs, in relation to the control group, as well as bacteria that could complicate the clinical picture.